Biochemical mechanism and biological effects of the inhibition of silent information regulator 1 (SIRT1) by EX-527 (SEN0014196 or selisistat) - Sylvain Broussy; Hanna Laaroussi; Michel Vidal (Taylor & Francis Group, 2020)
The human sirtuin silent information regulator 1 (SIRT1) is a NAD+-dependent deacetylase enzyme. It deacetylates many protein substrates, including histones and transcription factors, thereby controlling many physiological and pathological processes. Several synthetic inhibitors and activators of SIRT1 have been developed, and some therapeutic applications have been explored. The indole EX-527 and its derivatives are among the most potent and selective SIRT1 inhibitors. EX-527 has been often used as a pharmacological tool to explore the effect of SIRT1 inhibition in various cell types. Its therapeutic potential has, therefore, been evaluated in animal models for several pathologies, including cancer. It has also been tested in phase II clinical trial for the treatment of Huntington's disease (HD). In this review, we will provide an overview of the literature on EX-527, including its mechanism of inhibition and biological studies.